EVALUASI PENERAPAN LAPORAN ARUS KAS BERDASARKAN STANDAR AKUNTANSI KEUANGAN ENTITAS TANPA AKUNTABILITAS PUBLIK (SAK ETAP) PADA PERUSAHAAN PT. AIR MANADO - Makasenggehe, Victoria M.K; Ilat, Ventje; Gamaliel, Hendrik (Universitas Sam Ratulangi, 2018)
The cash flow report presents information on historical changes in cash and cash equivalents of the entity, which shows separately the changes that occur during one period of operating, investing and funding activities. The main purpose of the cash flow statement is the financial position report provides information on net cash inflows in a period, the results of the three main activities of the company are operations, investments and funding. SAK ETAP provides many facilities for companies compared to PSAK with more complex reporting provisions. In accordance with the scope of SAK ETAP, this standard is intended to be used by entities without public accountability (entities that do not have significant public accountability; and do not publish general-purpose financial statements). The presence of Entity Accounting Standards without Public Accountability (SAK ETAP) is expected to provide convenience for PT. Air Manado in presenting financial statements. The purpose of SAK ETAP itself is to provide facilities for small and medium scale entities. In accordance with SAK-ETAP, Entities without intended public accountability are entities that do not have significant public accountability and publish general-purpose financial reports for external users. This study uses a type of descriptive research - comparative. The results showed that PT. Air Manado has implemented financial statements in accordance with applicable standards but there are still items or elements in the cash flow statement that have not fully implemented the Entity Financial Accounting Standards without Public Accountability (SAK ETAP) in the cash flow statement. Keyword : SAK ETAP, Cash Flow Report,Financial Accounting,PT. Air Manado,Public Accountability